China urbanizing : impacts and transitions - Wu, Weiping, 1965-; Gao, Qin, 1977- (City in the twenty-first century book series., 2023)
"This book captures the impact of China's sweeping urbanization on its socioeconomic welfare, environment and resources, urban form and lifestyle, and population and health. The book provides new perspectives to understand China's transitions underway and the gravity of its progress in the context of demographic shifts and climate change"--